2015
DOI: 10.1515/atd-2015-0068
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Interaction Patterns in the Focus Group Interview

Abstract: This paper is based on the analysis of a focus group interview of a moderator and a group of undergraduate students on the topic of self-regulation of learning. The purpose of the investigation was to identify interaction patterns that appeared in the talk of participants and the moderator. In the stream of communication two rudimentary interaction patterns were recognized. The first pattern was named the Catalogue. It consists of a sequence of turns of participants who respond to a request of the moderator an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For example, Gibson (2003) introduced the concept of participation shift , which encompasses the turn-by-turn transformation of the participation framework in multi-party interactions. Gavora (2015) identified two interaction patterns— Catalogue and Domino 4 —in moderated focus groups, and Gatica-Perez et al (2012) studied dynamic processes in small groups from a multimodal perspective, taking into consideration contextual features like conversational attention, turn taking and conversational floor as well as practices for addressing or interrupting other participants. Further research for describing these complex relationships has been conducted by Onwuegbuzie et al (2009) who suggested the so-called “micro-interlocutor analysis” (p. 7) as a qualitative framework, using Conversation Analysis as a key method.…”
Section: Methodological Approaches For Studying Dynamics In Group Int...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Gibson (2003) introduced the concept of participation shift , which encompasses the turn-by-turn transformation of the participation framework in multi-party interactions. Gavora (2015) identified two interaction patterns— Catalogue and Domino 4 —in moderated focus groups, and Gatica-Perez et al (2012) studied dynamic processes in small groups from a multimodal perspective, taking into consideration contextual features like conversational attention, turn taking and conversational floor as well as practices for addressing or interrupting other participants. Further research for describing these complex relationships has been conducted by Onwuegbuzie et al (2009) who suggested the so-called “micro-interlocutor analysis” (p. 7) as a qualitative framework, using Conversation Analysis as a key method.…”
Section: Methodological Approaches For Studying Dynamics In Group Int...mentioning
confidence: 99%
“…In addition, participants might form and change alliances to achieve communicative actions. There are some suggestions for applying Conversation Analysis as a useful tool for studying group discussions on the micro-level of interaction, e.g., in order to analyze how group members organize turn taking activities (e.g., Gavora, 2015 ). Furthermore, Positioning Theory and its roots in discourse analysis is also used as a method to analyze multiparty interaction (e.g., Hirvonen, 2016 ).…”
Section: Introductionmentioning
confidence: 99%